Staff views of an opportunistic chlamydia testing pilot in a primary health organisation - McKernon S; Azariah S (CSIRO Publishing, 2013)
INTRODUCTION: The Auckland chlamydia pilot was one of three pilots funded by the Ministry of Health to trial implementation of the 2008 Chlamydia Management Guidelines prior to national roll-out. AIM: To assess what elements in the testing programme pilot worked best for staff and to determine how an opportunistic testing programme could be better configured to meet staff needs and preferences. METHODS: A staff survey listed key chlamydia testing tasks in chronological order, and service interventions supporting these tasks. Staff were asked to rate each task on its difficulty prior to the pilot, and then on the difference the pilot had made to each task. They were also asked to rate service interventions on their usefulness during the pilot implementation. RESULTS: The survey had a response rate of 94%. The testing tasks posing the greatest difficulties to staff were those involving patient interactions (41%) and management of follow-up (52%). About 70% of staff felt tasks were improved by the pilot. Staff considered the three most useful service interventions to be a chlamydia-specific template created for the practice management system, provision of printed patient resources, and regular team discussions with other staff. DISCUSSION: A significant proportion of staff reported difficulties with routine tasks required for opportunistic testing for chlamydia, highlighting the need to involve staff during programme design. Practice nurse-led approaches to future opportunistic testing programmes should be considered as nurses had a more positive response to the pilot and nurse-led approaches have been shown to be successful overseas.